Improving Rapid Diagnosis And Treatment In Emergency Medical Services: Integration Of Point-Of-Care Testing, Pharmacological Support, And Quality Assurance (The Review of Diabetic Studies, 2025)
Background: With increasing pressure on Emergency Medical Services to provide timely and precise diagnosis, along with effective prehospital treatment, Point of Care Testing, pharmacotherapy, and Quality Assurance are solutions to address the increasing demands. Methods: A systematic review of literature published in the last five years, from 2020 to 2026, was done using databases like PubMed, EMBASE, Cochrane Library, and Web of Science. Results: Forty-two studies were included in the systematic review. POCT had sensitivity >92% and specificity >89% for emergencies. Structured pharmacotherapy reduced errors by 34%. QA also showed an improvement of 27% in clinical performance. Conclusion: With the integration of POCT, pharmacotherapy, and QA, EMS patient outcomes are likely to improve. Future studies on training and standardization are recommended.